Green electrosynthesis strategies of SnO catalysts for enhanced photodegradation of 2,4-dichlorophenol - Torlaema, T. A.M.; Jaafar, Nur Farhana; Mutalib, A. A.A.; Lahuri, A. H. (John Wiley and Sons Inc, 2025)
The electrogeneration of SnO using an environmentally friendly approach was assessed by utilizing three different electrolytes: N,N-dimethylformamide (DMF), plant extract (PE), and a combination of PE with a deep eutectic solvent (PE-DES). The catalysts were characterized through FTIR, XRD, BET surface area analysis, and UV–Vis DRS to determine their structural and optical properties. The photocatalytic degradation of 2,4-dichlorophenol (2,4-DCP) was then evaluated for each catalyst under visible light exposure. At pH 3, SnO-PE-DES exhibited the highest degradation rate of 99.22%, making it the most efficient catalyst. SnO-DMF showed a degradation efficiency of 93.81%, while commercial SnO achieved 86.60%. The degradation efficiency of SnO-PE alone was only 23.46%, but incorporating DES significantly improved its performance. This enhancement is attributed to DES's ability to promote a more organized SnO structure, increasing the surface area and improving interactions with 2,4-DCP molecules. Due to its environmentally friendly synthesis and outstanding photocatalytic activity, SnO-PE-DES was selected for further optimization studies. This catalyst demonstrates great potential for photocatalytic applications in wastewater treatment. Its impressive performance under visible light, coupled with its eco-friendly synthesis, makes it a promising candidate for large-scale environmental remediation projects powered by solar energy.